A Critical Role of Bacterioferritin in Salmonella pullorum-Induced IFN-β Expression in DF-1 Cells - Xu, Zhichao; Qin, Yao; Wang, Yongqiang; Li, Xiaoqi; Cao, Hong; Zheng, Shijun J. (Frontiers in Microbiology, 2016)
Salmonella enterica serovar Pullorum (S. pullorum) causes pullorum disease in poultry and results in great economic losses to the poultry industry. Although an eradication program has been successfully performed in some countries, it remains a major threat to countries with poor poultry disease surveillance. Currently there are no effective control measures for pullorum disease except eradication. In particular, the pathogenesis of S. pullorum infection is still largely unknown. Here we identified bacterioferritin (Bfr) as a major antigen of S. pullorum to elicit a humoral immune response. Furthermore, we demonstrate that Bfr induces activation of IFN-β promoter and mRNA expression in DF-1 cells, and that the amino acids 1–50 form a critical domain involved in IFN-β expression. Moreover, we found that the p38 MAPK signaling pathway was essential for Bfr-induced IFN-β expression. Importantly, S. pullorum-induced IFN-β expression was totally abolished by deficiency of Bfr in the bacteria, indicating that Bfr plays a critical role in S. pullorum induced IFN-β expression in DF-1 cells. Our findings provide new insights into the molecular mechanisms of the host response to S. pullorum infection.